Search for Classical Cepheids in Galactic Open Clusters and Calibration of the Period–Wesenheit–Metallicity Relation in the Gaia Bands - Huajian Wang; Ye Xu; Zehao Lin; Chaojie Hao; Dejian Liu; Yingjie Li (The Astronomical Journal)
It is beneficial to calibrate the period–Wesenheit–metallicity relation (PWZR) of Delta Cephei stars (DCEPs), i.e., classical Cepheids, using accurate parallaxes of associated open clusters (OCs) from Gaia data release 3 (DR3). To this aim, we obtain a total of 43 OC–DCEPs (including 33 fundamental mode, 9 first overtone mode, and 1 multimode DCEPs) and calibrate the PWZR as ${W}_{G}=(-3.356± 0.033)(logP-1)+(-5.947± 0.025)$ + (−0.285 ± 0.064)[Fe/H]. The concurrently obtained residual parallax offset in OCs, zp = −4 ± 5 μ as, demonstrates the adequacy of the parallax corrections within the magnitude range of OC member stars. By comparing the field DCEPs’ DR3 parallaxes with their photometric parallaxes derived by our PWZR, we estimated the residual parallax offset in field DCEPs as zp = −15 ± 3 μ as. Using our PWZR, we estimate the distance modulus of the Large Magellanic Cloud to be 18.482 ± 0.040 mag, which aligns well with the most accurate published value obtained through geometric methods.